CASE REPORTSAtopic allergy and chronic inflammation of the oral mucosa in a 4-year-old boy after heart transplantation – diagnostic and therapeutic difficulties - Machura, Edyta; Chodór, Beata; Kleszyk, Magdalena; Pindycka-Piaszczyńska, Małgorzata; Chrobak, Ewelina; Białkowski, Jacek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
In recent years, we have been observing an increased proportion of atopic diseases in children after solid organ transplantation. The pathogenesis of post-transplantation allergy is not completely understood and probably involves several factors, including immunosuppressive therapy. In this paper we present a case of 3-year old boy, after orthotopic heart transplantation at 6 months of age, with symptoms of food allergy associated with atopic dermatitis and changes in the orofacial area. The mentioned symptoms and elevated levels of total and specific IgE occurred with a year of transplant. Because of failure to achieve remission after typical allergy therapy we suspected that the reason of allergy in this case can be immunosuppressive therapy.